Production of fluorinated fengycins in Bacillus spp. Issue Volume 1(2019)Issue A (8th March 2019) - Phelan, Aoife; Murphy, Cormac; Cobb, Steven; Gimenez-Ibanez, Diana
Abstract : Bacillus spp. produces lipopeptides that are of pharmaceutical and agricultural interest and include iturins, surfactins and fengycins. Their antimicrobial mechanism has been well studied but the role of the lipid chain and its biosynthesis is relatively unknown, especially in fengycin. In this project, we aim to fully understand the mechanisms of fengycin's antimicrobial activity and generate new fengycins with fluorine in the lipid chain. We have already produced fluorinated lipopeptides via precursor-directed biosynthesis using fluorinated amino acids. The Bacillus genome was sequenced by MicrobesNG and a total of 34 gene clusters were identified, of which 19 were fully characterised using anti SMASH. Genes within the fengycin cluster were cleaved during the sequencing process and iturin biosynthetic genes were also present. Four fatty acyl-CoA ligases within the genome were identified using Artemis in an aim to heterologously express them, and carry out activity assays with fluorinated lipid tails. Lipopeptide production was optimised by altering culture conditions (pH, aeration and temperature) and it was found that 37 °C is the optimum temperature for biosynthesis.